KEWENANGAN NOTARIS DALAM HAL MEMBUAT AKTA PARTIJ (CONTOH KASUS PUTUSAN MAHKAMAH AGUNG NOMOR: 1003 K/PID/2015) - Rio Utomo Hably; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2019)
Partij deed is a type of deed that can be made by a notary public official who is authorized by the state to perform services in society. Notary public as a public official who contains an authentic description of all events or events that are seen, experienced, and witnessed by the Notary himself. Notary Deed must contain what is desired by both parties in the agreement. The notary public only has the role of providing perfect proof of strength through the deed he made if later the parties to the deed disputed in court. In practice problems often arise including the issue of notary responsibility and notary authority as happened in the deed of party, how the authority of the Notary in Making Partij Deed (Example of Supreme Court Decision Case Number: 1003 K / PID / 2015) is a problem that is discussed. Descriptive research methods, using secondary data and primary data as supporting data, are analyzed qualitatively. The results of the study illustrate that the Notary does not follow under Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary.